1996
DOI: 10.1128/iai.64.8.3093-3100.1996
|View full text |Cite
|
Sign up to set email alerts
|

Intermedilysin, a novel cytotoxin specific for human cells secreted by Streptococcus intermedius UNS46 isolated from a human liver abscess

Abstract: A novel cytotoxin (intermedilysin) specific for human cells was identified as a cytolytic factor of Streptococcus intermedius UNS46 isolated from a human liver abscess. Intermedilysin caused human cell death with membrane blebs. Intermedilysin was purified from UNS46 culture medium by means of gel filtration and hydrophobic chromatography. The purified toxin was resolved into major and minor bands of 54 and 53 kDa, respectively, by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. These proteins react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(79 citation statements)
references
References 42 publications
(31 reference statements)
1
77
0
Order By: Relevance
“…PLY (the closest CDC relative of ILY) was shown to facilitate pneumococcal invasion/ penetration and proliferation in alveolar cells and, following bacteremia (31), damage endothelial cells of the blood brain barrier (44) and cause meningitis in the mouse (36). The cytolytic characteristics and steric molecular structure of ILY are similar to those of other CDCs (24,25,29), although ILY shows an unusual and perhaps significant species specificity for human cells and recognizes an alternative cell membrane receptor to cholesterol, the receptor molecule for typical CDCs (24,25). It has recently been reported that the ILY receptor is CD59, a glycosylphosphatidylinositol (GPI)-anchored cell surface protein (10) production levels and deep-seated infection has been shown (27) together with modulation of the PMN functions by ILY (22), the role of ILY in infection by S. intermedius was evaluated using an ily knockout mutant and complementation strain in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PLY (the closest CDC relative of ILY) was shown to facilitate pneumococcal invasion/ penetration and proliferation in alveolar cells and, following bacteremia (31), damage endothelial cells of the blood brain barrier (44) and cause meningitis in the mouse (36). The cytolytic characteristics and steric molecular structure of ILY are similar to those of other CDCs (24,25,29), although ILY shows an unusual and perhaps significant species specificity for human cells and recognizes an alternative cell membrane receptor to cholesterol, the receptor molecule for typical CDCs (24,25). It has recently been reported that the ILY receptor is CD59, a glycosylphosphatidylinositol (GPI)-anchored cell surface protein (10) production levels and deep-seated infection has been shown (27) together with modulation of the PMN functions by ILY (22), the role of ILY in infection by S. intermedius was evaluated using an ily knockout mutant and complementation strain in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previously we reported a human-specific pore-forming cytolysin, intermedilysin (ILY) secreted from a strain of S. intermedius originally isolated from the human liver (25,26). ILY is a member of the cholesterol-dependent cytolysins (CDC) which include streptolysin O (SLO) (4,19), and it has been shown to directly cause cell membrane damage in human erythrocytes and in cell lines derived from the major organs involved in deep-seated infections by S. intermedius (25). Therefore, ILY has been suggested as a potentially important virulence factor of this species (17,25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…AGS are opportunist human pathogens capable of causing liver and brain abscesses, dentoalveolar infections and endocarditis (Jacobs et al, 1995). The secreted intermedilysin (ILY) of S. intermedius binds complement receptor CD59 on human cells and forms cytotoxic pores, but only in the presence of sufficient levels of cholesterol (Nagamune et al, 1996;Farrand et al, 2008;Heuck et al, 2010;Johnson et al, 2013). ILY damages host tissues and immune cells to promote bacterial survival and dissemination (Nagamune et al, 1996(Nagamune et al, , 2000.…”
Section: Intermedilysinmentioning
confidence: 99%
“…The secreted intermedilysin (ILY) of S. intermedius binds complement receptor CD59 on human cells and forms cytotoxic pores, but only in the presence of sufficient levels of cholesterol (Nagamune et al, 1996;Farrand et al, 2008;Heuck et al, 2010;Johnson et al, 2013). ILY damages host tissues and immune cells to promote bacterial survival and dissemination (Nagamune et al, 1996(Nagamune et al, , 2000. ILY is considered to be a major virulence factor required for adherence to and invasion of human liver cells (Sukeno et al, 2005).…”
Section: Intermedilysinmentioning
confidence: 99%